A Micropolymorphism Altering the Residue Triad 97/114/156 Determines the Relative Levels of Tapasin Independence and Distinct Peptide Profiles for HLA-A*24 Allotypes - Soumya Badrinath; Heike Kunze-Schumacher; Rainer Blasczyk; Trevor Huyton; Christina Bade-Doeding (Journal of Immunology Research)
While many HLA class I molecules interact directly with the peptide loading complex (PLC) for conventional loading of peptides certain class I molecules are able to present peptides in a way that circumvents the PLC components. We investigated micropolymorphisms at position 156 of HLA-A*24 allotypes and their effects on PLC dependence for assembly and peptide binding specificities. HLA-A*24:06156Trp and HLA-A*24:13156Leu showed high levels of cell surface expression while HLA-A*24:02156Gln was expressed at low levels in tapasin deficient cells. Peptides presented by these allelic variants showed distinct differences in features and repertoire. Immunoprecipitation experiments demonstrated all the HLA-A*24/156 variants to associate at similar levels with tapasin when present. Structurally, HLA-A*24:02 contains the residue triad Met97/His114/Gln156 and a Trp156 or Leu156 polymorphism provides tapasin independence by stabilizing these triad residues, thus generating an energetically stable and a more peptide receptive environment. Micropolymorphisms at position 156 can influence the generic peptide loading pathway for HLA-A*24 by altering their tapasin dependence for peptide selection. The trade-off for this tapasin independence could be the presentation of unusual ligands by these alleles, imposing significant risk following hematopoietic stem cell transplantation (HSCT).